High-Performance Ternary Organic Solar Cells Enabled by Synergizing Fullerene and Non-fullerene Acceptors - Jiang, Yuanyuan; Zhu, Xiaozhang (Organic Materials, 2021)
With the development of the non-fullerene acceptors (NFAs), the use of ternary organic photovoltaic devices based on a fullerene acceptor and a NFA is now widespread, and the merits of both acceptor types can be fully utilized. However, the effective approach of enhancing device performance is adjusting the charge dynamics and the thin-film morphology of the active layer via introducing the second acceptor, which would significantly impact the open-circuit voltage, the short-circuit current, and the fill factor, thus strongly affecting device efficiency. The functions of the second acceptor in a ternary organic solar cell with a fullerene acceptor and a NFA are summarized here. These include a broader absorption spectrum; formation of a cascade energy level or energy transfer; modified thin-film morphology including phase separation, effects on crystallinity, size, and purity of domain; and vertical distribution along with improved charge dynamics like exciton dissociation and charge transport, collection, and recombination. Then, we discuss the hierarchical morphology in ternary solar cells, which may benefit device performance, and the outlook of the ternary device.
Keywords: ternary organic solar cells; fullerene acceptors; non-fullerene acceptors; power conversion efficiency